2007
DOI: 10.1038/nn1936
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila kinesin required for synaptic bouton formation and synaptic vesicle transport

Abstract: The morphological transition of growth cones to synaptic boutons characterizes synaptogenesis. Here we have isolated mutations in immaculate connections (imac; CG8566), a previously uncharacterized Drosophila gene encoding a member of the Kinesin-3 family. Whereas earlier studies in Drosophila implicated Kinesin-1 in transporting synaptic vesicle precursors, we find that Imac is essential for this transport. An unexpected feature of imac mutants is the failure of synaptic boutons to form. Motor neurons lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
213
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(233 citation statements)
references
References 50 publications
17
213
1
Order By: Relevance
“…We specifically focused on Kif5C and Kif3A kinesin complexes and have identified several proteins that are potentially targeted to synapses. Previous studies identified some cargos of Kif5C, including GABA receptors (22), axonal synaptic vesicle precursors (23), APP-containing vesicles (24,25), TrkB vesicles (26), mitochondria (23,(27)(28)(29)(30)(31), AMPAR vesicles (32), and mRNA/protein complexes (33,34). Kif3 was shown to transport fodrin-associating vesicles in cultured superior cervical ganglion neurons (35), Ncadherin in the developing mouse brain (36) and axonal voltagegated potassium channel in cultured hippocampal neurons (37).…”
Section: Discussionmentioning
confidence: 99%
“…We specifically focused on Kif5C and Kif3A kinesin complexes and have identified several proteins that are potentially targeted to synapses. Previous studies identified some cargos of Kif5C, including GABA receptors (22), axonal synaptic vesicle precursors (23), APP-containing vesicles (24,25), TrkB vesicles (26), mitochondria (23,(27)(28)(29)(30)(31), AMPAR vesicles (32), and mRNA/protein complexes (33,34). Kif3 was shown to transport fodrin-associating vesicles in cultured superior cervical ganglion neurons (35), Ncadherin in the developing mouse brain (36) and axonal voltagegated potassium channel in cultured hippocampal neurons (37).…”
Section: Discussionmentioning
confidence: 99%
“…Dynein mediates the minus-end-directed transport of SVs (Koushika et al 2004;. Neurons also use KIF1A to transport neuropeptide-carrying dense core vesicles (DCVs) from the cell soma to the synaptic region (Jacob and Kaplan 2003;Pack-Chung et al 2007), again in a bidirectional manner in concert with dynein (Barkus et al 2008;Goodwin et al 2012).Although null alleles of KIF1A are lethal, forward genetic studies in Drosophila and Caenorhabditis elegans have generated many useful reduction-of-function alleles for investigating the consequences of impaired SV and DCV transport and/or for studying the functions of KIF1A's various domains (Hall and Hedgecock 1991;Pack-Chung et al 2007;Barkus et al 2008;Maeder et al 2014). Recent C. elegans studies have also identified rare gain-of-function unc-104 (KIF1A) alleles (Wu et al 2013;Zheng et al 2014).…”
mentioning
confidence: 99%
“…Axonal microtubules are oriented with their plus-ends pointing toward the synaptic region (Burton and Paige 1981;Heidemann et al 1981;Baas and Lin 2011). The plus-end-directed kinesin motor KIF1A carries SVs outward to the stable SV clusters at synapses (Hall and Hedgecock 1991;Okada et al 1995;Pack-Chung et al 2007). However, for reasons not immediately clear, the transport is bidirectional, alternating between minus-end-directed retrograde transport and plus-end-directed anterograde transport, with plus-end transport ultimately dominating to achieve SV accumulation at synapses .…”
mentioning
confidence: 99%
See 2 more Smart Citations